Effect of Fluid Flow Direction on Charging of Multitube Thermal Energy Storage for Flat Plate Solar Collectors - Ramalingam Senthil (Center of Biomass & Renewable Energy, Diponegoro University, 2021)
Flat plate solar collector plays a significant role in domestic water heating due to the ease of operation and maintenance. Thermal energy storage with phase change materials is used to store heat energy. The thermal performance of paraffin wax-based multitube latent heat storage with a flat plate solar collector is investigated experimentally. The present work focuses on the fluid flow direction for charging and discharging in a vertical multitube-based thermal storage unit. The charging process took about four hours, with a fluid flow rate of 0.02 kg/s at about 70°C. The flat plate solar collector's thermal efficiency is 56.42% for the fluid flow rate of 0.02 kg/s at the average solar radiation of about 600 W/m2. During the discharge process, there was an increase in water temperature by 40°C at a fluid flow rate of 0.01 kg/s in 30 minutes. The 25-liters of water is circulated to discharge the stored heat. The heat storage effectiveness is varied between about 0.4 and 0.75. During the discharge, the flow of water from the center to the periphery showed about a 1.7% higher temperature than that of the water from the periphery to the center. For charging the heat storage, the preferred fluid flow mode is from the periphery to the center. The employment of latent heat storage with a solar collector is beneficial for our thermal needs after sunshine hours.